2009
DOI: 10.1093/nar/gkp164
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of hypothetical genes in Desulfovibrio vulgaris leads to improved functional annotation

Abstract: Hypothetical (HyP) and conserved HyP genes account for >30% of sequenced bacterial genomes. For the sulfate-reducing bacterium Desulfovibrio vulgaris Hildenborough, 347 of the 3634 genes were annotated as conserved HyP (9.5%) along with 887 HyP genes (24.4%). Given the large fraction of the genome, it is plausible that some of these genes serve critical cellular roles. The study goals were to determine which genes were expressed and provide a more functionally based annotation. To accomplish this, expression p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 64 publications
0
21
1
Order By: Relevance
“…Stress-specific responses include the upregulation of the hcp gene (encoding hydroxylamine reductase) during nitrite stress, the Na + /H + antiporter gene (nhaC2) in alkalinity stress, and genes involved in exopolysaccharide biosynthesis in biofilms during growth on a steel surface 73 . However, much of the divergence in stress responses is attributable to changes in the expression of a large number of genes with unknown functions, many of which genes are unique to SRMs 74 . Thus, a refined understanding of the specificity of stress responses warrants efforts to characterize these genes of unknown functions.…”
Section: Functional Gene Arraysmentioning
confidence: 99%
“…Stress-specific responses include the upregulation of the hcp gene (encoding hydroxylamine reductase) during nitrite stress, the Na + /H + antiporter gene (nhaC2) in alkalinity stress, and genes involved in exopolysaccharide biosynthesis in biofilms during growth on a steel surface 73 . However, much of the divergence in stress responses is attributable to changes in the expression of a large number of genes with unknown functions, many of which genes are unique to SRMs 74 . Thus, a refined understanding of the specificity of stress responses warrants efforts to characterize these genes of unknown functions.…”
Section: Functional Gene Arraysmentioning
confidence: 99%
“…to oxygen or heat shock [Chhabra et al, 2006]. Moreover, the genome annotation status was improved by expression of (conserved) hypothetical genes [Elias et al, 2009], and the central metabolism was studied by flux analysis [Tang et al, 2007]. With sulfate-reducing bacteria other than Desulfovibrio spp., research has rarely advanced from the physiological to the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…So far, more than 20 complete genomes of SRM are available. The analysis of the genome of the deltaproteobacterium Desulfovibrio vulgaris Hildenborough revealed that 34% of it encodes hypothetical and conserved hypothetical proteins of unknown function (19,27). Among them, several are conserved in anaerobes, suggesting that they serve critical cellular functions in the anaerobic way of life of D. vulgaris Hildenborough and other SRM.…”
mentioning
confidence: 99%